2015
DOI: 10.1002/jps.24309
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Intercellular Junctions by Cyclic-ADT Peptides as a Method to Reversibly Increase Blood–Brain Barrier Permeability

Abstract: It is challenging to deliver molecules to the brain for diagnosis and treatment of brain diseases. This is primarily due to the presence of the blood-brain barrier (BBB), which restricts the entry of many molecules into the brain. In this study, cyclic ADT peptides (ADTC1, ADTC5, and ADTC6) have been shown to modify the BBB to enhance the delivery of marker molecules (e.g., 14C-mannitol, Gd-DTPA) to the brain via the paracellular pathways of the BBB. The hypothesis is that these peptides modulate cadherin inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 42 publications
4
61
0
1
Order By: Relevance
“…22 Similarly, HAV4 peptide enhanced the in vivo brain delivery of Gd-DTPA better than HAV6 in Balb/c mice as detected by MRI. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Similarly, HAV4 peptide enhanced the in vivo brain delivery of Gd-DTPA better than HAV6 in Balb/c mice as detected by MRI. 26 …”
Section: Discussionmentioning
confidence: 99%
“…22,23 Recently, both HAV6 (Table 1) and ADTC5 peptides have been shown to enhance the brain delivery of both small and large molecules into the brain of rats and mice. 24-26 …”
Section: Introductionmentioning
confidence: 99%
“…Mgf was analysed in both the A and B compartments to calculate the value of Papp (Figure 11). The TEER values were continuously recorded while performing experiment, showing miniscule reduction (i.e., <10%) in TEER value on the treated cells wrt the control cells which indicated that there was slight opening of the tight junctions of Caco-2 cells, signifying paracellular transport (Sha et al, 2005;Chen et al, 2015;Laksitorini et al, 2015).…”
Section: Bidirectional Permeability Assaymentioning
confidence: 99%
“…Dengan demikian, kehadiran BBB menjadi tantangan tersendiri dalam proses penghantaran obat menuju sel target. Salah satu cara untuk meningkatkan sistem penghantaran obat adalah dengan meningkatkan porositas tight junction dengan menghambat interaksi kadherin-kadherin pada adherens junction [6].…”
Section: Pendahuluanunclassified